Clinical indications and scanning protocols for chest CT in children with cystic fibrosis: a survey of UK tertiary centres - Gilchrist, Francis J (BMJ Paediatr Open, 2018)
OBJECTIVES: Chest CT is increasingly used to monitor disease progression in children with cystic fibrosis (CF) but there is no national guideline regarding its use. Our objective was to assess the indications for undertaking chest CT and the protocols used to obtain scans. DESIGN, SETTING AND PARTICIPANTS: An electronic questionnaire was developed to assess clinicians views on chest CT in children with CF. It included general questions on perceived benefits and specific questions about its role in five clinical scenarios. It was sent to the clinical lead in 27 UK paediatric CF centres. A separate questionnaire was developed to collect the technical details of chest CT in children with CF. It was sent to the superintendent radiographer at each of the 27 centres. RESULTS: Responses were obtained from 27 (100%) clinical leads and 22 (81%) superintendent radiographers. 93% clinicians reported chest CT useful in monitoring disease progression and 70% said it frequently altered management. Only 5 (19%) undertook routine scans. To aid diagnosis, 81% performed chest CT in non-tuberculous mycobacterial disease and 15% in allergic bronchopulmonary aspergillosis. There was wide variation in the perceived need for and/or timing of chest CT in children with reduced lung function with no benefit from intravenous antibiotics, new cystic changes on chest X-ray, and lobar collapse. The radiographers reported using a mixture of helical (volumetric) and axial scans depending on the clinical question, the age and the cooperation of the child. When indicated, 6 (27%) used sedation and 16 (73%) general anaesthetic. Only 1 (5%) used intravenous contrast routinely and 3 (14%) obtained expiratory images routinely. CONCLUSIONS: There is marked variation in the use of chest CT in children with CF and in the scan protocols. The lack of a national guideline is likely to be contributing to this lack of standardisation.